ВПЛИВ МАГНІТНОГО ЗВ’ЯЗКУ МІЖ ПАРАЗИТНИМИ ІНДУКТИВНОСТЯМИ КОНДЕНСАТОРІВ РІЗНИХ ТИПІВ НА ВНОШУВАНЕ ПРОТИЗАВАДНИМ ФІЛЬТРОМ ЗГАСАННЯ НЕСИМЕТРИЧНОЇ ЗАВАДИ - Гурін, В.К.; Юрченко, О.М.; Пілінський, В.В. (Інститут електродинаміки НАН України, Київ, 2025)
The influence of magnetic coupling between the parasitic inductances of Y capacitors of an RFI filter on the level of the filter insertion loss was studied. It is shown that the magnetic coupling mentioned above significantly worsens the attenuation introduced by the filter at frequencies from 150 kHz to 30 MHz. Mutually perpendicular, parallel, and end-to-end arrangement of capacitors relative to each other was analyzed as one of the methods of reducing the magnetic coupling between parasitic inductances of Y capacitors. It is shown that an increase in the distance between the said capacitors increases the attenuation introduced by the filter into common mode noise in the frequency range of 150 kHz to 30 MHz by 10 to 15 dB. References 27, Figures 9.